The Optimal Period of Staged Bilateral Total Knee Arthroplasty Procedures under Enhanced Recovery: A Retrospective Study - Kaibo Sun; Jinkui Pi; Yuangang Wu; Yi Zeng; Jiawen Xu; Limin Wu; Mingyang Li; Bin Shen (Orthopaedic Surgery, 2023)
Objective The implications of the interval of staged bilateral total knee arthroplasty (TKA) procedures for postoperative complications and costs are not clear. We aimed to determine the optimal time interval between the two stages of bilateral TKA procedures under the enhanced recovery after surgery (ERAS) protocol. Methods This retrospective study of collected data included bilateral TKA cases under the ERAS protocol performed between 2018 and 2021 at the West China Hospital of Sichuan University. The staged time was subdivided into three groups according to the interval between the first TKA and second contralateral TKA: group 1: 2‐ to 6‐month, group 2: 6‐ to 12‐month, and group 3: >12 months. The primary outcome was the incidence of postoperative complications. The secondary outcomes were the length of hospital stay (LOS), hemoglobin (Hb) decrease, hematocrit (Hct) decrease, and albumin (Alb) decrease. Results We analyzed 281 patients who underwent staged bilateral TKAs between 2018 and 2021 at the West China Hospital of Sichuan University. Regarding postoperative complications, there were no statistically significant differences among the three groups (P = 0.21). For the mean LOS, the 6‐ to 12‐month group had a significantly shorter LOS compared with the 2‐ to 6‐month group (P < 0.01). There was also a significant decrease in Hct of the 2‐ to 6‐month group compared with the 6‐ to 12‐month group and the >12 months group (P = 0.02; P < 0.05, respectively). Conclusion Staging the second arthroplasty for more than a half year seems to offer a reduction in the rate of postoperative complications and LOS under ERAS protocol. ERAS shortens the interval of staged bilateral TKA by at least 6 months for patients who might receive their second surgery without the need to wait for an extended period.